Hierarchy of Influence on the Implementation of Search Engine Optimization in the Tribun-Bali.com Newsroom - Anggara, Oktava; Gelgel, Ni Made Ras Amanda; Purnawan, Ni Luh Ramaswati (JURNAL KOMUNIKASI INDONESIA, 2024)
Technological disruption has driven changes in the media and journalism industry, affecting the workflow in the newsroom. One emerging practice in the newsroom is the application of search engine optimization (SEO). This practice raises concerns about editorial decisions being directed toward topics that are "popular and easily clickable". Tribun-Bali.com is one of the biggest news portals in Bali that implements SEO. This study aims to depict the hierarchy of influences on the implementation of SEO in the Tribun-Bali.com newsroom. It is a qualitative descriptive study that employs interview methods with key informants. Utilizing the hierarchy of influences theory proposed by Pamela J. Shoemaker and Stephen D. Reese, the findings of this research reveal that the organizational influence level dominates the implementation of SEO in the editorial space of Tribun-Bali.com, and it is closely related to the company's economic goal. It is followed by the influences of media routine, extra-media, ideology, and individual level.